An array of 2D Magnetic Micro Force Sensors for Life Science Applications. (2015) - Praprotnik, J.; Ergeneman, O.; Chatzipirpiridis, G.; Weidlich, A.; Blaz, S.; Pané, S.; Nelson, B.J.
Abstract: This paper reports a 2D magnetic micro force sensor. The design consists of an array of SU-8 cantilevers incorporating electroplated ferromagnetic material and a Hall sensor array. The passive moving parts with magnetic readout enable robust and sensitive operation. The presented device has a detection limit of 30 μN and a range up to 1 mN. A not well-known material in MEMS community polyurethane was used as a protection layer encapsulating the whole device while interfering minimally with the operation. Cantilevers were characterized for their dynamic response by a laser Doppler vibrometer and 2D force calibration is performed using commercial force sensors. The presented sensor array can be used in life science applications and MEMS testing enabling parallel measurements in 2-D.